Evidence-based medicine and precision medicine: Complementary approaches to clinical decision-making. Issue 2 (17th August 2018) - Chow, Ngai; Gallo, Lucas; Busse, Jason W
Abstract: Evidence-based medicine is widely promoted for decision-making in health care and is associated with improved patient outcomes. Critics have suggested that evidence-based medicine focuses primarily on groups of patients rather than individuals, but often fail to consider subgroup analyses, N-of-1 trials, and the incorporation of patient values and preferences. Precision medicine has been promoted as an approach to individualize diagnosis and treatment of diseases through genetic, biomarker, phenotypic, and psychosocial characteristics. However, there are often high costs associated with personalized medicine, and high-quality evidence is lacking for effectiveness in many applications. For the potential of personalized medicine to be realized, it must adhere to the principles of evidence-based medicine: (1) evidence in isolation is not sufficient to make clinical decisions—patient's values and preferences as well as resource implications must be considered, and (2) there is a hierarchy of evidence to guide clinical decision-making and studies at lower risk of bias are likely to provide more trustworthy findings.